(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND Idiopathic pulmonary fibrosis (IPF) differs substantially from other idiopathic interstitial pneumonias regarding disease trajectory and the appropriate management strategies, making meticulous diagnosis essential. However, patient characteristics and clinical practice vary between clinical trials, and real life and registries provide the opportunity to critically analyse current clinical practices in order to ultimately improve patient care. ​ METHODS: We aimed to identify characteristics of our baseline IPF cohort at initiation of a web-based registry for patients with idiopathic interstitial pneumonia. Baseline and 6-month follow-up data from all consecutive IPF patients consulting at our centre over 2 years were analysed. RESULTS Forty IPF patients were included for baseline and 23 for longitudinal analysis. Besides many similarities to other IPF populations, our cohort included considerably fewer women. Forced vital capacity impairment in our cohort was more severe and mortality prediction poorer than in clinical trials, which emphasises the importance to confirm the applicability of clinical trial results with data from real life settings. CONCLUSION Registries for rare diseases such as IPF are a valuable resource for studying the course of the disease under current compliance with diagnostic and treatment guidelines and to appreciate local epidemiological particularities.